PREDICTORS OF HYPOXEMIA IN BRONCHIOLITIS IN A SAMPLE OF IRAQI INFANTS - Nafie Hameed, Numan; AL-Janabi, Muhi K.; Omar Hamad, Cawes (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Bronchiolitis is the first episode of wheezing associated with low grade fever, rhinitis, tachypnea, and increasing respiratory effort in a previously healthyinfant during the winter months, and it is the most common lower respiratory tract infection in infancy.Objectives: This study is designed to analyze the clinical signs and symptoms alone or as combinations as possible predictors of severe hypoxemia in infants withbronchiolitis.Patients and methods: This is a prospective study, which was carried out on 96 infants with a mean age of 7.74 ±3.72 months who were admitted to Children Welfare Teaching Hospital in Medical City-Baghdad with bronchiolitis during the period from 1st October 2006 to the 15th March 2007. They are divided into two groups: group one 46 cases (oxygen saturation (SaO2